The indigenous knowledge and attitudes of older persons living in Khayelitsha and Phillipi regarding the management of minor health ailments - Zonke, Mbuyiseli Simon (Department of Public Health and Family Medicine, 2014)
Includes bibliographical references (leaves 91-94).